2001
DOI: 10.1038/sj.thj.6200072
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor coagulation pathway and blood cells activation state in renal insufficiency

Abstract: Renal insufficiency is associated to an activation of the tissue factor coagulation pathway, to a platelet, monocyte and endothelial activation/injury and to a deficient tissue-factor induced response to activated protein C which culminate in end-stage disease and are increased by hemodialysis runs. This contributes to linked coagulation and cellular conditions for an enhanced atherosclerosis progression. Due to the TF pathway activation, the therapeutic use of recombinant TFPI should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 0 publications
0
30
1
2
Order By: Relevance
“…In support of our in vitro studies, renal insufficiency was associated with activation of the TF coagulation pathway and endothelial injury in end-stage disease aggravated by the HD treatment (17,31,37). A significant linear correlation between the PMNL priming index and TF expression in HUVEC exposed to PMNL suggests that the procoagulant state of HUVEC depends directly on the PMNL priming state.…”
Section: Discussionmentioning
confidence: 49%
“…In support of our in vitro studies, renal insufficiency was associated with activation of the TF coagulation pathway and endothelial injury in end-stage disease aggravated by the HD treatment (17,31,37). A significant linear correlation between the PMNL priming index and TF expression in HUVEC exposed to PMNL suggests that the procoagulant state of HUVEC depends directly on the PMNL priming state.…”
Section: Discussionmentioning
confidence: 49%
“…Gondouin et al 40 showed the ability of IS and indole acetic acid to induce TF production through the aryl hydrocarbon receptor pathway, which was associated with increased procoagulant activity. CKD patients have elevated levels of soluble TF 41 and kynurenin, which like IS, belongs to the large group of the indoles and is associated with increased soluble TF levels and hypercoagulability in CKD patients. 42 Furthermore, endothelial microparticles, considered as markers of endothelial dysfunction, are shed on endothelial activation and involved in the regulation of coagulation by activating the TF pathway, 43 whereas both IS and pCS have been shown to elicit endothelial microparticle release in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies indicate that thrombosis occurs in the area of arterial stenosis caused by atherosclerotic incidents [5].…”
Section: Introductionmentioning
confidence: 99%